Jumanji - Johnston, Joe, 1950-; Kroopf, Scott; Teitler, William; Williams, Robin, 1951-2014; Dunst, Kirsten, 1982-; Grier, David Alan, 1956 June 30-; Hann-Byrd, Adam; Hunt, Bonnie; Sony Pictures Home Entertainment (Firm) ([Culver City, California] : Sony Pictures Home Entertainment, 2017)
When young Alan Parrish discovers a mysterious board game, he doesnt realize its unimaginable powers, until he is magically transported before the startled eyes of his friend, Sarah, into the untamed jungles of Jumanji! There he remains for 26 years until he is freed from the games spell by two unsuspecting children. Now a grown man, Alan reunites with Sarah and together with Judy and Peter tries to outwit the games powerful forces.
Title from web page.
Originally released as a motion picture in 1995.
Wide screen (1.85:1).
Keywords: Board games -- Drama; Magic -- Drama